Design like Apple : seven principles for creating insanely great products, services, and experiences - Edson, John, 1966- (Hoboken, N.J. : Wiley, 2012)
"Apple sees design as a tool for creating beautiful experiences that convey a point of view down to the smallest detail--from the tactile feedback of keyboard to the out-of-the-box experience of an iPhone package. And all of these capabilities are founded in a deep and rich embrace of what it means to be a designer. Design Like Apple uncovers the lessons from Apple's unique approach to product creation, manufacturing, delivery, and customer experience"--Provided by publisher.
Design Makes All the Difference -- Design the Organization -- The Product Is the Marketing -- Design Is Systems Thinking -- Design Out Loud -- Design Is for People -- Design Like Apple.
Includes bibliographical references and index.
Keywords: Apple Computer, Inc; Apple Computer, Inc; Apple Computer, Inc; Apple Computer, Inc; Apple Computer, Inc; Product design; Customer services; Marketing; Product design; Customer services; Marketing; TECHNOLOGY & ENGINEERING -- Industrial Design -- Product; Customer services; Marketing; Product design; Product design; Customer services; Marketing; Electronic books